The Reporting Flow of Budget Accountability at the Regional House of Representatives (DPRD) of Malang City - Yogivaria, Doni Wirshandono (International Journal of Economics Studies, 2025)
The reporting flow of budget accountability in the Regional House of Representatives (DPRD) of Malang City plays a crucial role in ensuring transparency and good governance in the management of public funds. This study examines the procedural framework and stages involved in the budget accountability process at DPRD Malang City. Using a qualitative approach, the research focuses on analyzing the responsibilities and obligations of DPRD members in reporting budget usage, as well as the systems and tools implemented to ensure accuracy and timeliness in the reporting process. Data were collected through a review of relevant literature, government regulations, and interviews with DPRD officials. The research findings highlight that the reporting flow involves several key stages: budget planning, execution, monitoring, and reporting. Each stage requires thorough documentation, which is reviewed and approved by various levels of authority within DPRD before submission to higher government bodies. Additionally, there are challenges faced in this process, including delays in documentation, lack of human resources with adequate financial expertise, and technical issues with digital reporting systems. The study recommends improvements in training for DPRD staff, better integration of technology in reporting systems, and more stringent oversight mechanisms to ensure the accountability process is conducted smoothly and efficiently. By addressing these challenges, DPRD Malang City can enhance its financial reporting practices, contributing to better public trust and ensuring proper utilization of public funds.